2018
DOI: 10.21273/jashs04495-18
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Aspects of Vernalization and Flowering in Long-day Storage Onion

Abstract: Vernalization is an important step for floral initiation in onion (Allium cepa), but our understanding of the minimum vernalization time for long-day storage onions to gain floral competence is limited. A series of time course experiments were conducted over 4 years to determine the effects of vernalization time on sprouting, scape emergence, and flowering in ‘Cortland’, ‘Sherman’, and CUDH2107. We found an endodormancy period is present in the bulbs of these cultivars that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
3
7
0
Order By: Relevance
“…While the treatment seems to have been effective at mitigating losses from disease pressure, the effect on root initiation was not as strong as in previous years. Uniformity in rooting time among varieties was poor relative to previous work and the performance of "Cortland" and "Sherman" was consistent with results reported by D'Angelo and Goldman [14] for the year 2015, which was also a year with high disease pressure. This observation supports an earlier observation that a 4-h hydrogen peroxide treatment may be less effective at breaking dormancy in bulbs that were subject to high disease pressure [14].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…While the treatment seems to have been effective at mitigating losses from disease pressure, the effect on root initiation was not as strong as in previous years. Uniformity in rooting time among varieties was poor relative to previous work and the performance of "Cortland" and "Sherman" was consistent with results reported by D'Angelo and Goldman [14] for the year 2015, which was also a year with high disease pressure. This observation supports an earlier observation that a 4-h hydrogen peroxide treatment may be less effective at breaking dormancy in bulbs that were subject to high disease pressure [14].…”
Section: Discussionsupporting
confidence: 82%
“…We have previously demonstrated that treatments with 10-30% hydrogen peroxide solutions serve to promote uniform endodormancy release and root initiation in "Cortland" and "Sherman" bulbs [14]. In this study, CUDH2107, "Sherman", and WEOS1 bulbs treated with a 15% hydrogen peroxide solution were effectively released from endodormancy as expected, with an average of 13.3 days to visible root growth.…”
Section: Comparison Of Vernalization Timessupporting
confidence: 76%
See 3 more Smart Citations